Prevention of peritoneal recurrence in high‐risk colorectal cancer and evidence of T4 status as a potential risk factor. Issue 10 (6th March 2018) - Kyang, Lee Shyang; Valle, Sarah J.; Alzahrani, Nayef A.; Morris, David L.
Abstract : Peritoneal metastasis (PM) following primary resection of colorectal cancer is common. The combined use of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy has significantly improved the survival outcome of patients with colorectal PM (CRPM). Diagnosing and treating early PM is essential as its extent is correlated with poorer outcomes. There are two novel therapies – second‐look surgery and synchronous hyperthermic intraperitoneal chemotherapy – that are proposed to prophylactically treat or intervene early in the disease process to reduce the incidence and adverse outcomes associated with PM. These strategies are limited to patients at high risk of developing CRPM, including those that had synchronous PM or ovarian metastases resected at primary tumour removal, or a perforated primary tumour. The data on advanced primary tumour (T4) as a prognostic factor for PM after primary resection suggest that T4a tumours are prognostically worse than T4b. This literature review outlines the evidence, feasibility and safety regarding the pre‐emptive treatments, as well as the relevance of T4a tumours as a risk factor for metachronous CRPM.